Kepribadian Pejabat Pemerintah Provinsi Sumatera Barat - Jumiati, Jumiati (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2003)
This research aimed at describing the personalities of Government officers in province of West Sumatera. For this purpose qualitative approach was used through â€œmean and percentageâ€ analysis.Â The finding of this research indicated that the personalities of Government officers in province of West Sumatera was in low grade, either in the level of general government or in those of instances and agencies. Â Kata Kunci: Kepribadian, Pejabat Pemerintah